The study of consumer behavior towards purchasing electrical products in Singapore. - Koh, Hwee Kiah. (2008)
Using random sampling, we seek to find out the factors affecting Singapore consumers' buying behaviour towards electrical products. These factors include price, quality, design, the effects of country-of-origin, location preferences, influence of marketing and payment method.